Prospect of Utilization of Microorganisms Streptomyces sp. and Trichoderma sp. in Supporting Sustainable Agriculture in the Age of Modern Agriculture - Arga Dwi Indrawan; Penta Suryaminarsih; Tri Mujoko (Nusantara Science and Technology Proceedings, 2021)
The geographical condition of Indonesia's agriculture in the tropics supports agricultural business throughout the year through agricultural intensification. Agricultural intensification brings benefits to agricultural productivity, but also causes farmers to be dependent on pesticides and inorganic fertilizers in excess, causing long-term degradation of agricultural land productivity. Susstainable Agriculture is an approach to increase agricultural productivity while still being friendly to the agricultural ecosystem. Sustainable agriculture can be achieved through the preservation of agricultural resources, one of which is the use of beneficial microorganisms. Stre ptomyces sp. and Trichoderma sp. is a multi-role microorganism as a supporter of plant growth, biological agent in pest control, and helps increase soil fertility. The use of these microorganisms has good prospects for sustainable modern agriculture in order to achieve food security but also has obstacles that need to be overcome through further research.